Própolis na produção de cachaça orgânica de qualidade - Montijo, Nayara Abrão [UNESP] (2014)
Regulations are being created worldwide to reduce the amount of antimicrobial residues in food and beverages, especially distilled alcoholic beverages, because contaminant microorganisms from fermentation process may infect and depreciate the product quality. This study aimed to evaluate the effect of propolis extracts, monensin-based synthetic antimicrobial and previous physical-chemical treatment of the broth to control contaminants in the fermentation process for the production of cachaça. We studied the effects on the activity of the Saccharomyces cerevisiae CA-11 and the composition of secondary metabolites and quality of the final distillate. The experiment was arranged in a completely randomized design in split splots with three replications, using main treatments (five antimicrobials) and secondary treatments (fermentation cycles). The main treatments were: control (untreated juice); sodium monensin; green propolis ethanolic extract (GPEE); brown propolis ethanolic extract (BPEE); physical-chemical juice treatment (PCT). Secondary treatments corresponded to five fermentation cycles. The amount of yeast cell and bud viability, and yeast bud rate during the fermentation were evaluated. The wines were analyzed for pH, total acidity, glycerol and alcohol content. Microbiological evaluations indicated that the sugarcane source used, presented with excellent quality, showing low number of contaminants in juice and wine.The compounds of cachaça quantified by gas chromatography were (acetaldehyde, acrolein, esters, ethyl carbamate, higher alcohols, isobutyl, isoamyl, methanol, propyl, volatile acidity). Ethanol levels produced by the yeast strain ‘CA-11’ in the fermentation were found to be around 6 to 7%, which are not statistically significant among treatments. The concentrations of the secondary compounds were met significantly below the limits of the Brazilian legislation ...